An analysis of juvenile law in Taiwan and some comparisons with the U.S - Jan, Lee -Jan (American journal of criminal justice, 1981)
Juveniles have been treated differently from adults in legal matters throughout Chinese history. However, a special comprehensive juvenile law was not published until 1962. The law deals with juvenile delinquents and potential delinquents, ages 12–18. Juveniles involved in espionage against the government are not protected by juvenile law. Juveniles in general have less due process protection compared to their counterparts in the U.S. However, this is compensated by the better trained judges in Taiwan. Cultural differences also resulted in Taiwan putting more emphasis on the family responsibility for the care and Supervision of juveniles.